2015
DOI: 10.1039/c4fo00901k
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic bioactivity of Alpinia officinarum (Hance) Farw Zingiberaceae can be attributed to the coexistance of curcumin, polyphenolics, dietary fibers and phytosterols

Abstract: Rhizoma A. officinarum (Hance) Farw, synonymously is called rhizoma galangae or smaller galangal (hereafter abbreviated as AO). Numerous studies reported that AO possesses anti-inflammatory, anticancer, chemoprotective, antibacterial, antifungal and diuretic properties. To understand whether AO exhibits antihyperlipidemic bioactivity and what is the mechanism of action, we performed chemical and animal studies using hamsters (age: 4 weeks, body weight: 45 ± 4 g). The grouping of the animals was as follows: con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
(35 reference statements)
1
14
1
Order By: Relevance
“…22 In contrast, our result has lower the level of this compound than A. officinarum (5 mg/g) from Taiwan as well. 35 The results of this study conform to the previous data which reported that Z. officinale was rich in 6-gingerol (245 µg/g DW). 25 Similarly, Puengphian and Sirichote 36 extracted 6-gingerol from Z. officinale using the supercritical CO 2 extraction method at 200 bar at 35°C and 230 bar at 40°C and reported 6-gingerol contents of 239 and 171 mg/g in the extract from the respective conditions.…”
Section: Discussionsupporting
confidence: 91%
“…22 In contrast, our result has lower the level of this compound than A. officinarum (5 mg/g) from Taiwan as well. 35 The results of this study conform to the previous data which reported that Z. officinale was rich in 6-gingerol (245 µg/g DW). 25 Similarly, Puengphian and Sirichote 36 extracted 6-gingerol from Z. officinale using the supercritical CO 2 extraction method at 200 bar at 35°C and 230 bar at 40°C and reported 6-gingerol contents of 239 and 171 mg/g in the extract from the respective conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Alpinia officinarum Hance (Zingiberaceae), commonly known as lesser galangal, is an important plant from the ginger family that originates in southern China and is cultivated in Southeast Asia [ 11 ]. Its rhizomes, which have a strong aromatic odour, have been used as Chinese folk medicine (usually called “Gao-liang-jiang”) for decades [ 12 ]. Numerous studies reported that A. officinarum possesses anti-inflammatory, anticancer, antibacterial, antifungal, antihyperlipidemic, antiemetic, and diuretic properties [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alpinia officinarum (lesser galangal) has been used for sexual dysfunction in traditional Persian medicine (Avicenna, ) for more than 10 centuries (Rezaeizadeh, Alizadeh, Naseri, & Ardakani, ). Several compounds that have been isolated from this plant show various effects, including antioxidant, antimicrobial and anti‐inflammatory effects (Hewage et al, ; Lin et al, ; Honmore et al, ). There are good safety profiles in other studies (Altman & Marcussen, ; Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds that have been isolated from this plant show various effects, including antioxidant, antimicrobial and anti‐inflammatory effects (Hewage et al, ; Lin et al, ; Honmore et al, ). There are good safety profiles in other studies (Altman & Marcussen, ; Lin et al, ). One of the main active components of A. officinarum is galangin which has been indicated in several studies to have a potent antioxidant activity (Kaushik, Yadav, Kaushik, Sacher, & Rani, ).…”
Section: Introductionmentioning
confidence: 99%